2017
DOI: 10.1073/pnas.1618706114
|View full text |Cite
|
Sign up to set email alerts
|

G9a drives hypoxia-mediated gene repression for breast cancer cell survival and tumorigenesis

Abstract: G9a is an epigenetic regulator that methylates H3K9, generally causing repression of gene expression, and participates in diverse cellular functions. G9a is genetically deregulated in a variety of tumor types and can silence tumor suppressor genes and, therefore, is important for carcinogenesis. Although hypoxia is recognized to be an adverse factor in tumor growth and metastasis, the role of G9a in regulating gene expression in hypoxia has not been described extensively. Here, we show that G9a protein stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
84
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 30 publications
6
84
1
Order By: Relevance
“…In solid tumors such as HCC, glycolysis is exacerbated by the protumorigenic hypoxic environment. (34) As recently found in breast cancer cells, (35) we observed that G9a protein levels were increased in HCC cells under hypoxia ( Fig. 5A and Supporting Fig.…”
Section: Cm-272 Inhibits the Growth And Metabolic Adaptation Of Hcc Csupporting
confidence: 85%
“…In solid tumors such as HCC, glycolysis is exacerbated by the protumorigenic hypoxic environment. (34) As recently found in breast cancer cells, (35) we observed that G9a protein levels were increased in HCC cells under hypoxia ( Fig. 5A and Supporting Fig.…”
Section: Cm-272 Inhibits the Growth And Metabolic Adaptation Of Hcc Csupporting
confidence: 85%
“…polyubiquitination and proteasomal degradation of G9a (45). In our experimental conditions, however, PHD1-3 knockdown failed to increase G9a and GLP protein levels under normoxia, while it clearly stabilizes HIF-1 or HIF-2 (Fig.1D).…”
mentioning
confidence: 55%
“…Pharmacological or genetic inhibition of G9a prevents tumorigenesis in mice [40, 41]. G9a is induced by hypoxia at both transcriptional and posttranslational levels in embryonic stem cells and cancer cells and may mediate hypoxia-induced gene repression through increasing dimethyl K9 of histone H3 in cancer cells [4143]. However, the direct effect of G9a on HIF transcriptional activity remains unknown.…”
Section: Regulation Of Hif Transcriptional Activity By Epigenetic Wrimentioning
confidence: 99%